Pediatric and Adolescent Nephrology Facing the Future: Diagnostic Advances and Prognostic Biomarkers in Everyday Practice - Taranta-Janusz, Katarzyna; Musiał, Kinga (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue entitled "Pediatric and adolescent nephrology facing the future: diagnostic advances and prognostic biomarkers in everyday practice" contains articles written in the era when COVID-19 had not yet been a major clinical problem in children. Now that we know its multifaceted clinical course, complications concerning the kidneys, and childhood-specific post-COVID pediatric inflammatory multisystem syndrome (PIMS), the value of diagnostic and prognostic biomarkers in the pediatric area should be appreciated, and their importance ought to increase.